Experimentation skills in primary school: an inventory of children's understanding of experimental design - Christopher Osterhaus; Susanne Koerber; Beate Sodian (EARLI, 2016)
Experimentation skills are a central component of scientific thinking, and many studies have investigated whether and when primary-school children develop adequate experimentation strategies. However, the answers to these questions vary substantially depending on the type of task that is used: while discovery tasks, which require children to engage in unguided experimentation, typically do not reveal systematic skills in primary school, choice tasks suggest an early use of adequate experimentation strategies. To acquire a more accurate description of primary-school experimentation, this article proposes a novel multiple-select paper-and-pencil inventory that measures children's understanding of experimental design. The two reported studies investigated the psychometric properties of this instrument and addressed the development of primary-school experimentation. Study 1 assessed the validity of the item format by comparing 2 items and an interview measure in a sample of 71 third- and fourth-graders (9- and 10-year-olds), while Study 2 investigated the reliability and the convergent validity of the inventory by administering it to 411 second-, third- and fourth-graders (8-, 9- and 10-year-olds) and by comparing children's performance in the 11-item scale to 2 conventional experimentation tasks. The obtained results demonstrate the reliability and validity of the inventory and suggest that a solid understanding of experimental design first emerges at the end of primary school.